2022
DOI: 10.3390/biomedicines10061229
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Small Nucleolar RNAs in B-Cell Malignancies

Abstract: Small nucleolar RNAs (snoRNAs) are responsible for post-transcriptional modification of ribosomal RNAs, transfer RNAs and small nuclear RNAs, and thereby have important regulatory functions in mRNA splicing and protein translation. Several studies have shown that snoRNAs are dysregulated in human cancer and may play a role in cancer initiation and progression. In this review, we focus on the role of snoRNAs in normal and malignant B-cell development. SnoRNA activity appears to be essential for normal B-cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…SnoRNAs, a homogeneous group of non-coding RNAs that guide modifications of ribosomal RNA, have emerged as important players contributors in cancer. 57 , 58 Unlike microRNAs and lncRNAs, they possess distinct characteristics. Numerous studies have demonstrated that snoRNAs can be utilized as diagnostic and prognostic biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SnoRNAs, a homogeneous group of non-coding RNAs that guide modifications of ribosomal RNA, have emerged as important players contributors in cancer. 57 , 58 Unlike microRNAs and lncRNAs, they possess distinct characteristics. Numerous studies have demonstrated that snoRNAs can be utilized as diagnostic and prognostic biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Germinal center, naïve, marginal zone and memory B-cells, peripheral blood B cells express a distinct snoRNA pattern with reduced SNORD116-1, SNORD116-23, SNORD116-29, SNORD94, and SNORA36A expression ( 76 ), indicating these snoRNAs may play a key role in B cell maturation and function. SnoRNAs derived from the DLK-DIO3 locus(containing 41 snoRNAs) were reduced whereas the expression of SNURF/SNRPN snoRNAs remained high in different types of B-cell malignancies compared to healthy B-cells ( 77 ). SNORA25 was reported to target 18S rRNA subunit (18S-801 and 18S:U814) and mediate the pseudouridylation of these residues ( 78 ).…”
Section: Snorna-mediated Immune Cell Function To Participate In Tumor...mentioning
confidence: 99%
“…In recent years, with the development of sequencing technology, more and more data show that snoRNAs are dysregulated in many diseases including hematological malignancies, solid tumors, hereditary diseases, and metabolic diseases (Williams and Farzaneh, 2012); (Liu et al, 2020a); (Verbeek et al, 2022). In a study of snoRNAs from 33 patients with acute myeloid leukemia, the probability of snoRNA dysregulation was not high, with only 9.3% of C/D box snoRNAs and 0.9% of H/ACA box snoRNAs found to be significantly increased or decreased (including some putative novel snoRNAs, using a rigorous 5% false discovery rate).…”
Section: Snornasmentioning
confidence: 99%